Autoimmune bullous diseases during COVID-19 pandemic: 2022 update on rituximab and vaccine - Pira, Anna; Sinagra, Jo Linda Maria; Moro, Francesco; Mariotti, Feliciana; Di Zenzo, Giovanni (Frontiers in Medicine, 2023)
Autoimmune bullous diseases are a heterogeneous group of life-threatening disorders associated with subepidermal or intraepidermal blistering that need prolonged and often aggressive immunosuppressive therapy. Due to skin barrier alteration and chronic treatments, patients are potentially at greater risk of infections, and are considered fragile. The impact of the COVID-19 pandemic on these patients has been heavy. Although a lot of progress has currently been made in terms of prevention and treatment of COVID-19, several issues emphasize the importance of this topic: i) the pandemic could be with us for many years; ii) outbreaks could always be upon us; and iii) a large proportion of patients is not vaccinated, so far. This review is a 2022 update that summarizes and discusses the pandemic’s burden on autoimmune bullous disease patients in term of i) susceptibility to COVID-19 infection; ii) relationship between infection and disease course and treatment; iii) possible effects of vaccination such as induction, exacerbation or relapse of autoimmune disease, with a specific focus on the impact of B-cell depletion therapy and adverse events of vaccination.